Numerical Simulation of Cold Rolled Steel Sheet Metal during Blanking Process - Pecháč, Peter; Sága, Milan; Sapieta, Milan (Manufacturing Technology Journal, 2018)
This paper presents numerical simulation of blanking process using finite element method and comparison of results obtained by analytical solution commonly used in engineering practice. The problem was modeled using axial symmetry. Experimental measurement was used to create multi-linear plastic material model. Results of numerical simulation were used to create history of blanking force vs. tool displacement.
Keywords: Blanking process; numerical; sheet metal